Role of Professional Learning Communities [PLCs] As A Mediator Between Transformational Leadership and Teacher Performance in The District of Aritao - Villanueva, Desiree Joyce (International Journal of Sustainability and Advanced Integrated Research, 2026)
Quality education is widely acknowledged as a crucial element in achieving the Sustainable Development Goal 4 (SDG 4). This study explored the role of Professional Learning Communities (PLCs) as a mediator between transformational leadership and teacher performance in the District of Aritao I. Specifically, the study aimed to understand the effects of transformational leadership on PLCs and teacher performance, as well as the mediating role of PLCs in enhancing teacher performance. This study employed a quantitative descriptive-correlational research design with mediation analysis. A structured questionnaire was used to gather data from 100 public school teachers selected through purposive sampling. Statistical tools such as frequency, percentage, weighted mean, standard deviation, Pearson correlation, regression analysis, and mediation analysis were used to analyze the gathered data. The findings indicated that transformational leadership, PLCs, and teacher performance were rated very highly by the respondents, with overall mean scores of 4.30, 4.31, and 4.28, respectively. The results further suggest that transformational leadership significantly influences PLCs and teacher performance. Similarly, PLCs significantly affected teacher performance and partially mediated the relationship between transformational leadership and teacher performance. These findings imply that effective leadership practices enhance collaboration, shared learning, and professional growth among teachers, leading to improved instructional performance among teachers. The study concluded that transformational leadership and active PLCs are important factors for improving teacher performance and educational quality. Therefore, it is recommended that leadership practices and collaborative professional learning activities be strengthened to enhance teacher effectiveness and support better educational outcomes in schools.
Keywords: Transformational Leadership; Professional Learning Communities; Teacher Performance; Educational Leadership; Professional Development